The Development of Teaching Materials for Islamic Religious Education Courses Based on Local Wisdom at Public State Universities - Usman,; Bahraeni,; Nurhilaliyah,; Rahman, Ananda Fathur (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to develop open educational materials for Islamic Religious Education (PAI) at public universities, grounded in diverse local values. The focus is on the creation and validation of teaching materials, incorporating local wisdom from Sulawesi and Mataram regions. The research adopts a Research and Development (R&D) approach, utilizing a 4-D model of development (Define, Design, Develop, Disseminate). The teaching materials, which integrate local values from Sulawesi (siri', pacce', pemmali, and pappaseng) and Mataram (karma, sesengak, perteke, and lelakak), were tested at a state university. The development process involved a team of validators, and the results demonstrated high validity. The findings suggest that the development of teaching materials integrating Islam with relevant local values can provide a more contextualized and meaningful educational experience for students. Consequently, this study is expected to offer guidance for other universities in formulating open PAI materials that effectively combine Islamic principles with local cultural values. Abstrak: Penelitian ini bertujuan untuk membuat bahan terbuka Pendidikan Agama Islam (PAI) di perguruan tinggi negeri berdasarkan nilai-nilai lokal yang beragam. Penelitian ini berfokus pada pembuatan bahan ajar pada Universitas Negeri Makassar dan Universitas Mataram yang berintegrasi pada nilai lokal dari kedua daerah. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan (R&D), dan menggunakan model pengembangan 4-D (Define, Design, Develop, Disseminate). Dua perguruan tinggi melakukan uji coba bahan ajar, yang menggabungkan kearifan lokal dari dua daerah - Sulawesi (siri', pacce', pemmali, dan pappaseng) dan Mataram (karma, sesengak, perteke, dan lelakak). Bahan terbuka dikembangkan oleh tim validator, dan hasilnya menunjukkan validitas yang tinggi. Dengan demikian, pengembangan bahan ajar dengan mengambil pendekatan yang mengintegrasikan Islam dengan nilai-nilai lokal yang relevan akan menghasilkan pengalaman pendidikan yang lebih kontekstual dan bermakna bagi siswa. Oleh karena itu, penelitian ini diharapkan dapat memberikan Arahan bagi perguruan tinggi lain dalam merumuskan bahan terbuka PAI yang menggabungkan Islam dengan nilai-nilai budaya lokal.